Perceptions of Micro Small and Medium Enterprise Managers in Financing Accessibility to the Formal Banking Institutions - Juardi, Juardi (Technium Social Sciences Journal, 2021)
Micro, Small and Medium Enterprises (MSMEs) play an important role in Indonesia’s economic recovery. This potential requires MSME actors to prepare various important aspects so that their business will grow, one of which is developing their business through Bank financing. However, the majority of MSME actors still do not have access to loans from the formal banking institutions. This research is intended to answer the questions why there are many MSMEs are still having difficulties in applying for loans to Banking institutions and what solutions must be done so that MSMEs can also get facilities for loans in order to develop their business. This is a qualitative research using a case study approach. Data collection was obtained from the results of semi-structured interviews with 10 MSME managers who have run the business for over 10 years with the various types of business namely snack and fries, sewing business, baby food, chicken porridge, and moslem clothing. The results of this study indicate that MSME managers in the North Bogor area still have difficulty accessing loans to formal Banking institutions due to 2 things, namely the low socio-economic conditions of MSME managers, as evidenced by not having a Bank account, not having collateral, and not having a partnership. Another thing is the problem of the educational background of MSME managers which is considered very low so that in general, they are not able to make good proposals, make financial reports, do not understand marketing problems and business development concepts. Therefore, the Banking sector is expected to simplify the requirements for MSME managers and provide guidance related to the professional management and development of MSMEs.